The equation `(x - i)/(x - 3) = 4` has to be solved.

`(x - i)/(x - 3) = 4`

=> x - i = 4*(x - 3)

=> x - i = 4x - 12

=> 3x = 12 - i

=> `x = 4 - i/3`

**The solution of the equation is **`x = 4 - i/3`

(x - i)/(x - 3) = 4

x - i = 4 (x - 3)

x - i = 4x - 12

x-4x = -12 - i

-3x = -12 - i

divide by -3

4- i/3

`(x-i)/(x-3) =4`

To cancel the fraction multiply, (x-3) on both sides.

- x - i = 4 (x - 3)

Distribute the 4.

- x - i = 4x - 12

Combine like terms (I moved the variables to one side & the numbers to the other side).

- x-4x = -12 - i

Simplify.

- -3x = -12 - i

Isolate x. Since '-3x' is multiplication, what is the opposite operation? (Division)--divide by -3 on both sides.

x=`(-12-i)/-3`

(x - i)/(x - 3) = 4

multiply by x-3 to cancel the fraction

x - i = 4 (x - 3)

distribute the 4 to x and -3

x - i = 4x - 12

now move like terms to the same side:

x-4x = -12 - i

-3x = -12 - i

divide by -3

`x = 4 - i/3`